Influenza A(H1N1)pdm09 Virus Infection in a Captive Giant Panda, Hong Kong - Paolo Martelli; Jade L.L. Teng; Foo-Khong Lee; Kai-Yan Yeong; Jordan Y.H. Fong; Suk-Wai Hui; Kwok-Hung Chan; Susanna K.P. Lau; Patrick C.Y. Woo (Emerging Infectious Diseases, 2019)
We report influenza A(H1N1)pdm09 virus infection in a captive giant panda in Hong Kong. The viral load peaked on day 1 and became undetectable on day 5, and an antibody response developed. Genome analysis showed 99.3%–99.9% nucleotide identity between the virus and influenza A(H1N1)pdm09 virus circulating in Hong Kong.